Assessment of autonomic response in 6–12-month-old babies during the interaction with robot and avatar by means of thermal infrared imaging. Issue 2 (15th March 2023) - Filippini, C.; Cardone, D.; Perpetuini, D.; Chiarelli, A.M.; Petitto, L.A.; Merla, A.
ABSTRACT: Since birth, infants have been immersed in a social environment, often surrounded by artificial-intelligent-agents (AIAs). However, there is a paucity of work on infants' psychophysiological responses, and their related interest, when interacting with AIAs. Here, the infants' psychophysiological responses during interactions with an embodied robot and a virtual human/avatar presented on a screen are investigated. The experimental paradigm consists of a robot producing socially communicative gestures to babies as compared to a virtual human producing socially communicative gestures and linguistic interactions, such as linguistic nursery rhymes in American Sign Language. Psychophysiological responses were measured using thermal infrared imaging technology that tracks changes in cutaneous temperature, enabling contactless investigation of human autonomic functions. Crucially, it permits first-time inferences about changes in infants' psychological, attentional, and emotional engagement in relation to agents and events in the world around them. Thermal signals analysis revealed a statistically significant difference in the infants' physiological response to robot and avatar interactions indicating important differences in each agent's ability to engage infants. Understanding infants' psychophysiological responses to AIAs during the first year of life, which is a crucial period for human learning, lays bare how AIAs may impact infants' emotional, social, and language learning and higher cognitive growth.